Efficiency Study Analysis of Electrical Energy in Container Stacking Equipment Rubber Tyred Gantry Crane (RTGC) Using Hybrid Energy Source Method - Maulana, Salam; Ramza, Harry; Sofwan, Agus (Green Publisher, 2024)
This research to perform Efficiency Study Analysis Of electrical energy In Container Stacking Equipment Rubber Tyred Gantry Crane (RTGC) Using Hybrid Energy Source Method. RTGC gets power supply from Engine Diesel Generator with capacity of 350 kW. However, Genset power source in RTGC has drawbacks, such as when RTGC condition does not move (stationary) can lead to waste of fuel on diesel engine drivers. the Hybrid Energy Source is one of the technology which combines electrical energy source from generators and batteries, The battery of hybrid system can obtain electric energy saving until 32%, where for the Hoist system 11,72 %, Trolley system 33,63 % dan Gantry system 7,58 %.